Halal Governance in Malaysia (Journal of Business Management and Accounting, 2016)
Malaysia is in a strategic location in the South East Asia for the halal Industry, with a predominant Muslim population. The halal certificate by the Department of Islamic Development (JAKIM) is recognized globally. The halal hub is confined within the parameters of governance support and cooperation, such as political will to improve in terms of public service, governance structure, policy and all related to systematic governance. This study discusses the halal governance issue and the halal governance in Malaysia. Data was collected through series of focus groups interviews which makes this study exploratory in nature. The study applies purposive sampling, as information is conveniently available from specific target groups. The paper shall serve a reference for the government halal authority, higher institutions and researchers toward development of halal industry in Malaysia and focussing on halal supply chain activities which involves ministry, department and agency roles.